The Art of Reading. - Gould, E., Di Yanni, R. (New York Random House, Inc., 1987)
The Art of Reading grows out of two interrelated convictions: that active, engaged reading develops the writers resources and resourcefulness, and that active, engaged writing stimulates and clarifies the readers responses to texts.
Keywords: Reading